Corrigendum to Recent advancement and assessment of green hydrogen production technologies [Renew. Sustain. Energy Rev. 189 (2024) 5?5/113941] (Renewable and Sustainable Energy Reviews (2024) 189(PA), (S1364032123007992), (10.1016/j.rser.2023.113941)) - Zainal B.S.; Jern K.P.; Mohamed H.; Ong H.C.; Fattah I.M.R.; Rahman S.M.A.; Nghiem L.D.; Mahlia T.M.I. (Elsevier Ltd, 2025)
The authors would like to make some minor modifications in response to comments received from readers post-publication. The following issues were raised, necessitating the rectification of misunderstandings in Section 3, Table 1, on Page 5. Due to numerous requests from readers who print the article in black and white, we will include the color names in Table 3 and rephrase some definitions to enhance clarity. We assure readers that the suggested modifications solely aim to clarify issues identified after publication. The text originally stated: Table 1: Different colours of hydrogen defined by the technologies used [11?14]. [Table presented] This should be corrected to: Table 1: Different colours of hydrogen defined by the technologies used [11?14]. [Table presented] 1Source: https://doi.org/10.1016/j.rser.2023.113635. 2Source: https://cyanh2.com/ The authors would like to apologise for any inconvenience caused. ? 2024 Elsevier Ltd